2001
DOI: 10.1016/s0550-3213(00)00681-7
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Monte Carlo algorithm for the double exchange model

Abstract: The Hybrid Monte Carlo algorithm is adapted to the simulation of a system of classical degrees of freedom coupled to non self-interacting lattices fermions. The diagonalization of the Hamiltonian matrix is avoided by introducing a path-integral formulation of the problem, in d + 1 Euclidean space-time. A perfect action formulation allows to work on the continuum Euclidean time, without need for a Trotter-Suzuki extrapolation. To demonstrate the feasibility of the method we study the Double Exchange Model in th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
62
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 110 publications
(74 citation statements)
references
References 33 publications
9
62
3
Order By: Relevance
“…We recall that in Ref. 26 it is shown that at J AF ϭ0, T/tϭ0.14 the transition is second order. Although we find a strengthening of this transition when ͉J AF ͉ grows, to confirm that it actually becomes of the first order would require a careful finite-size scaling analysis that is beyond the scope of this work.…”
Section: B Finite Temperature Resultsmentioning
confidence: 76%
See 4 more Smart Citations
“…We recall that in Ref. 26 it is shown that at J AF ϭ0, T/tϭ0.14 the transition is second order. Although we find a strengthening of this transition when ͉J AF ͉ grows, to confirm that it actually becomes of the first order would require a careful finite-size scaling analysis that is beyond the scope of this work.…”
Section: B Finite Temperature Resultsmentioning
confidence: 76%
“…We have extended the previous studies to finite temperatures by using the hybrid Monte Carlo method reported elsewhere, 26 which allows to thermalize 16ϫ16ϫ16 clusters in reasonable computer time. We have studied the model ͑1͒, on the cubic lattice of side L with periodic boundary conditions, using the grand-canonical ensemble ͑4͒.…”
Section: B Finite Temperature Resultsmentioning
confidence: 99%
See 3 more Smart Citations